2021
DOI: 10.3389/fcvm.2021.667446
|View full text |Cite
|
Sign up to set email alerts
|

Glutaminolysis: A Driver of Vascular and Cardiac Remodeling in Pulmonary Arterial Hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a decimating ailment described by chronic precapillary pulmonary hypertension, an elevated mean pulmonary arterial pressure with a normal pulmonary capillary wedge pressure, and a raised pulmonary vascular resistance resulting in increased right ventricular afterload culminating in heart failure and death. Current PAH treatments regulate the vasodilatory/vasoconstrictory balance of pulmonary vessels. However, these treatment options are unable to stop the progression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 103 publications
0
14
0
Order By: Relevance
“…This study builds on an earlier report that mGluR5 is abundantly expressed in the RV 34 by examining its functional role in the heart in the setting of PAH. PI3K/AKT and P38MAPK signalling result in increased cell survival, hyperproliferation, myocyte hypertrophy, excessive inflammatory responses and fibrosis, which characterize remodelling in PAH 10,35 (Figure 7). AKT is a primary mediator of the PI3K signalling cascade 36 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study builds on an earlier report that mGluR5 is abundantly expressed in the RV 34 by examining its functional role in the heart in the setting of PAH. PI3K/AKT and P38MAPK signalling result in increased cell survival, hyperproliferation, myocyte hypertrophy, excessive inflammatory responses and fibrosis, which characterize remodelling in PAH 10,35 (Figure 7). AKT is a primary mediator of the PI3K signalling cascade 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary arterial hypertension‐induced cardiac remodelling involves changes in organ‐level hemodynamics to tissue stiffening, altered myocyte contractility and dysregulations in energetics 6–9 . Pulmonary arterial hypertension‐associated dysregulations in energetics (metabolic dysregulation) involving the anaplerotic use of glutamate (in glutaminolysis) drive PAH‐induced maladaptive cardiac remodelling 10 . Admittedly, increased glutaminolysis has been reported in the RV of PAH rat models and human PAH patients 11 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A global cellular metabolomics overview suggests that a set of altered mitochondrial metabolites contributes to the pathogenesis of PH [ 40 , 41 ]. Studies have revealed that cells of the pulmonary vasculature have a strong dependence on glutamine, which leads to excessive proliferation [ 42 ]. In cells, glutamine is the critical amino acid in several biochemical reactions, and is required for glutamate synthesis by glutaminolysis.…”
Section: Mitochondrial Metabolic Pathways In Pulmonary Hypertensionmentioning
confidence: 99%